2020
DOI: 10.3389/fgene.2020.558557
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanisms and Candidate Drugs for COVID-19 Based on the Connectivity Map Database

Abstract: Background: The coronavirus disease 2019 (COVID-19) has become a worldwide public health crisis. At present, there are no effective antiviral drugs to treat COVID-19. Although some vaccines have been developed, late-stage clinical trials that allow licensure by regulatory agencies are still needed. Previous reports have indicated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV are highly homologous and both use angiotensin-converting enzyme 2 (ACE2) as the receptor to enter cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…In comparison with other studies which employed similar computational approach for drug repurposing based on transcriptome reversal [ 27 , 28 , 29 , 31 ], we observed only a minor or no overlap of the drug candidate lists. Shared candidates were ADRA1B antagonists (nortriptyline in our study), as well as ACE inhibitor perindopril and NR1I2 agonists (econazole and ritonavir in our study) that were also identified by El-Hachem et al [ 30 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In comparison with other studies which employed similar computational approach for drug repurposing based on transcriptome reversal [ 27 , 28 , 29 , 31 ], we observed only a minor or no overlap of the drug candidate lists. Shared candidates were ADRA1B antagonists (nortriptyline in our study), as well as ACE inhibitor perindopril and NR1I2 agonists (econazole and ritonavir in our study) that were also identified by El-Hachem et al [ 30 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Several in silico drug repurposing studies based on a transcriptome reversal approach have already been published in the context of COVID-19 [ 27 , 28 , 29 , 30 , 31 ]. However, one common issue in such studies is a complete lack or insufficiency of the criteria for inclusion of datasets in the analysis which may then produce misleading results.…”
Section: Introductionmentioning
confidence: 99%
“…amantadine, rimantadine) are thought to disrupt lysosomal trafficking, thereby impeding the release of SARS-CoV-2 ribonucleic acid (RNA) into the cell (Araújo et al, 2020[ 2 ]), and by inhibiting conductance of the envelope (E) protein (Aranda Abreu et al, 2020[ 1 ]). Acyclovir, a nucleotide analog antiviral, was found as a candidate drug for COVID-19 by potentially counteracting gene expression changes observed after SARS-CoV-2 infection (Li and Yang, 2020[ 16 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In a bid to identify underlying mechanisms and candidate drugs for COVID-19, an analysis of differentially expressed genes that co-express with ACE2 indicated by the expression of RNAs isolated from bronchoalveolar lavage fluid cells of patients with COVID-19 by functional enrichment and hub gene cluster analyses were undertaken [ 11 ]. Using the connectivity map database with transcriptome profiles of patients with COVID-19, candidate drugs were identified, one of which was amantadine.…”
Section: Adamantanes Against Sars-cov-2: In Vitro and Preclinical Investigationsmentioning
confidence: 99%